Cryopreservation of caprine ovarian tissue using glycerol and ethylene glycol - Rodrigues, Ana Paula Ribeiro (2004)
Cryopreservation of ovarian tissue may be a potential alternative for the conservation of genetically superior animals, including high milk- and meat-producing goat breeds. However, until now, no information was available concerning the cryopreservation of preantral follicles (PF) enclosed in caprine ovarian tissue. The objective of the present study was to evaluate the structural and ultrastructural characteristics of caprine PF after exposure to and cryopreservation of ovarian tissue in 1.5 and 3 M glycerol (GLY) and ethylene glycol (EG). At the slaughterhouse, each ovarian pair from five adult mixed breed goats was divided into nine fragments and randomly distributed into treatment groups. One fragment was immediately fixed for histological examination and ultrastructural analysis, after slaughter (control). Four of the ovarian fragments were equilibrated at 20 °C for 20 min in 1.8 ml of MEM containing 1.5 or 3 M GLY or EG for a toxicity test and the final four fragments were slowly frozen using these cryoprotectants at the concentrations above. After toxicity testing and freezing/thawing, the ovarian fragments were fixed for histological examination. Histological analysis showed that after toxicity testing and cryopreservation of the ovarian tissue in GLY or EG at both concentrations, the percentage of normal PF was significantly lower than controls. Ultrastructural analysis of PF frozen in 1.5 and 3 M GLY, as well as 3 M EG demonstrated that these follicles remained morphologically normal. In conclusion, we demonstrated cryopreservation of caprine PF in ovarian tissue.